Kesiapan Kerja Dimediasi oleh Pengalaman Kerja Magang - Nur Rahmah Wahyuddin; Mifta Farid Salam; Edy Jumady; Yana Fajriah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the influence of the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Internship Program and soft skills on the work readiness of students at Universitas Ichsan Sidenreng Rappang, with internship experience as a mediating variable. The research employed a quantitative approach using Structural Equation Modeling (SEM) with AMOS. The study population consisted of 139 students who participated in the MBKM Internship Program in batches I and II, with samples determined through purposive sampling. The results reveal that the MBKM Internship Program has a positive and significant effect on both internship experience and students’ work readiness. Soft skills have a positive and significant effect on internship experience but do not directly influence work readiness. Furthermore, internship experience has a positive and significant effect on work readiness and acts as a mediating variable in the relationship between the MBKM program and soft skills with work readiness. This study provides practical contributions for students in optimizing internship experiences and soft skill development, for universities in evaluating MBKM program implementation, and for industries in designing internship programs that are relevant to labor market demands